THE ROLE OF THE EARLY DIAGNOSIS OF AUTOSOMAL RECESSIVE POLYCYSTIC KIDNEY DISEASE IN FETUSES- CASE STUDY - Livrinova, Vesna; Jovanovska, Viktorija; Samardjiski, Igor; Daneva Markova, Ana; Simeonova Krstevska, Slagjana; Petrovski, Ljupcho; Janevska, Vesna; Jovanovikj, Rubens; Plasheska Karanfilska, Dijana; Todorovska, I.; Shabani, A.; Komina, Selim; et al. (SHMSHM - AAMD, 2018)
ABSTRACT Introduction: The autosomal recessive polycystic kidney disease (ARPKD) is a rare disorder that is present in 1:20,000 babies. A fetal death may occur due to a severe oligohydramnios, or neonatal death caused by pulmonary insufficiency. The aim of the case study presentation is to point out the importance of the ultrasound diagnosis as early as possible in the pregnancy, so that the right decision is made by the parents and by the gynecologist. Methods: The methods used in this case include ultrasound, invasive diagnosis- amniocentesis and chorionic villus sampling, cytopathologic analysis and PCR amplification and sequencing of PKHD1 gene in the parents’ blood, amniotic fluid and chorionic villi. Results: The patient is 29 years old women, fourth pregnancy, previous two labors on time with caesarean section, both of the babies died in the neonatal period and are subject to post-mortem examination. The findings from the post-mortem examination shown a suspicion for autosomal recessive polycystic kidney disease (ARPKD). After the second result of the post-mortem examination, the parents were examined for having a mutation in the PKHD1 gene and it was confirmed that both of them are having this mutation. The third pregnancy ended with an induced abortion because the amniocentesis confirmed a fetus having a homozygote for ARPKD. In the fourth pregnancy a chorionic villus sampling was performed and a fetus was found with a heterozygote for ARPKD and the pregnancy was successful with a viability of the fetus. Conclusion: The timely intervention of gynecologist can prevent unfavorable effects- Caesarean section of matured fetuses that then usually exist in the first two months, because dialysis is the only therapy, temporarily until kidney transplantation takes place. This leads to emotional and medical consequences suffered by the parents.